Update on the Role of Rifaximin in Digestive Diseases - Dumitrascu, Dan Lucian; Bakulin, Igor; Berzigotti, Annalisa; Cravo, Marília; Gombošová, Laura; Lukas, Milan; Pietrzak, Anna; Remes-Troche, José María; Romero-Gómez, Manuel; Balmori, Mercedes Amieva; Gonçalves, Tiago Cúrdia; Hamzaoui, Lamine; et al. (Journal of gastrointestinal and liver diseases, 2023)
Various environmental factors affecting the human microbiota may lead to gut microbial imbalance and to the development of pathologies. Alterations of gut microbiota have been firmly implicated in digestive diseases such as hepatic encephalopathy, irritable bowel syndrome and diverticular disease. However, while these three conditions may all be related to dysfunction of the gut-liver-brain axis, the precise pathophysiology appears to differ somewhat for each. Herein, current knowledge on the pathophysiology of hepatic encephalopathy, irritable bowel syndrome, and diverticular disease are reviewed, with a special focus on the gut microbiota modulation associated with these disorders during therapy with rifaximin. In general, the evidence for the efficacy of rifaximin in hepatic encephalopathy appears to be well consolidated, although it is less supported for irritable bowel syndrome and diverticular disease. We reviewed current clinical practice for the management of these clinical conditions and underlined the desirability of more real-world studies to fully understand the potential of rifaximin in these clinical situations and obtain even more precise indications for the use of the drug.
Keywords: jaterní encefalopatie; Hepatic Encephalopathy; rifaximin; syndrom dráždivého tračníku; Diverticular Diseases; Rifaximin; Humans; lidé; rifamyciny; Irritable Bowel Syndrome; Rifamycins; divertikulární nemoci